Effect of propolis on glycemic control in patients with type 2 diabetes: an updated systematic review and meta-analysis of randomized controlled trials. Issue 7 (20th May 2021) - Mosallanezhad, Zahra; Clark, Cain; Bahreini, Fatemeh; Motamed, Zahra; Mosallanezhad, Abdolhamid; Hosseini, Seyedeh Fatemeh; Shaban-Khalaf, Aneseh; Sohrabi, Zahra
Abstract : Purpose: The purpose of this systematic review and meta-analysis was to investigate the efficacy of propolis on glycemic indices in type 2 diabetic patients. Design/methodology/approach: Web of science (ISI), Embase, Scopus and PubMed were systematically searched to find randomized controlled trials (RCTs) assessing the effects of propolis intake on glycemic controls in type 2 diabetic patients, from inception up to September 1, 2020. A random-effects model was used to pool weighted mean difference (WMD). Meta-regression was performed to detect the potential sources of inter-study heterogeneity. Findings: Seven trials were included in the meta-analysis. Compared to controls, propolis intake significantly improved serum fasting blood sugar (FBS) (WMD = −13.62 mg/dl, 95% CI = [−23.04, −4.20], P = 0.005, I2 = 58.5%) and hemoglobin A1C (HbA1c) (WMD = −0.52%, 95% CI = [−0.86, −0.18], P = 0.002, I2 = 64.0%). In contrast, receiving propolis did not change serum insulin (WMD = −1.46 (uIU/ml), 95% CI = [−2.94, 0.02], P = 0.05, I2 = 75.0%) and homeostatic model assessment for insulin resistance (HOMA-IR) (WMD = −0.98 (%), 95% CI = [−2.00, 0.04], P = 0.06, I2 = 82.3%) compared to controls. Originality/value: The present meta-analysis demonstrated that propolis intake significantly reduces serum FBS and HbA1c in diabetic patients but does not alter serum insulin and HOMA-IR. Further large-scale RCT's are needed to approve these effects.